Electrochemical investigation of thermically treated graphene oxides as electrode materials for vanadium redox flow battery. (1st June 2015) - Di Blasi, O.; Briguglio, N.; Busacca, C.; Ferraro, M.; Antonucci, V.; Di Blasi, A.
Highlights: Graphene oxide is synthesized at high temperatures in a reducing environment. Treated graphene oxide-based electrodes are prepared by the wet impregnation method. Electrochemical performance is evaluated as a function of the physico-chemical properties. Abstract: Thermically treated graphene oxides (TT-GOs) are synthesized at different temperatures, 100 °C, 150 °C, 200 °C and 300 °C in a reducing environment (20% H2 /He) and investigated as electrode materials for vanadium redox flow battery (VRFB) applications. The treated graphene oxide-based electrodes are prepared by the wet impregnation method using carbon felt (CF) as support. The main aim is to achieve a suitable distribution of the dispersed graphene oxides on the CF surface in order to investigate the electrocatalytic activity for the VO 2+ /VO2 + and V 2+ /V 3+ redox reactions in the perspective of a feasible large area electrodes scale-up for battery configuration of practical interest. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) are carried out in a three electrode half-cell to characterize the electrochemical properties of the TT-GO-based electrodes. Physico-chemical characterizations are carried out to corroborate the electrochemical results. The TT-GO sample treated at 100 °C (TT-GO-100) shows the highest electrocatalytic activity in terms of peak to peak separation (Δ E = 0.03 V) and current density intensity (∼0.24 A cm −2 at 30 mV/s) both toward the VO 2+ /VO2 + and V 2+ /V 3+ redox reactions. This result is correlated to the presence of hydroxyl (OH) and carboxyl (COOH) species that act as active sites. A valid candidate is individuated as effective anode and cathode electrode in the perspective of electrodes scale-up for battery configuration of practical interest.